Timing of growth zone formations in otoliths of the snapper, Chrysophrys auratus, in subtropical and temperate waters differ and growth follows a parabolic relationship with latitude - Wakefield, Corey; Potter, I.; Hall, N.; Lenanton, R.; Hesp, S. (Oxford University Press 2009, 2017)
Chrysophrys auratus was collected from one sub-tropical and two temperate regions spanning >2400 km along the coast of Western Australia (∼23.5–35.5° S). Marginal increment analysis demonstrated that, while a single opaque zone is formed in the otoliths of C. auratus each year, the period of deposition varies among regions. An opaque zone was formed in May to early September in the sub-tropical upper west coast, and thus when water temperatures were declining to their minima. In contrast, opaque zone formation occurred 3 months later in August to December in the temperate lower west and south coasts, when water temperatures were rising from their minima. The length and age distributions differed markedly among populations of C. auratus, with the strongest year classes varying among the three regions. Thus, it is likely that year class strength of C. auratus throughout its distribution along the coast of Western Australian is mostly related to local environmental conditions. Chrysophrys auratus grew far less rapidly and attained a smaller size in the warmer upper west coast than in the cooler temperate regions of the lower west and south coasts. A collation of data on C. auratus from ten populations in Australia and three in New Zealand showed that growth is greatest towards the mid-latitudes of its geographic range, i.e. at ∼31° S. Estimates of mean lengths at specified ages thus exhibit a parabolic relationship with latitude, with reduced growth (i.e. edge-of-range effects) occurring towards the latitudinal margins of the distribution of this sparid.